Effects of low-temperature acclimation on morphological and physiological indices of banana seedlings - Baysal, F. (Emirates Journal of Food and Agriculture, 2022)
Climate change has become the most important factor limiting the banana cultivation area, especially in countries with subtropical climates. To assess the effect of cold stress on banana, twenty-eight global and local cultivated clones were used for morphological and physio-biochemical evaluation. Methods: The banana clones were produced from shoot tips under in vitro conditions. When the plants were 20-25 cm in height and 5-6 leaves, they were transferred to climate-controlled rooms. The temperature of the testing room was gradually decreased every three days (from 28ºC day/22ºC night to 4ºC day/-1ºC night). After the seedlings remained at these temperatures, the temperature of the room was increased every three days (from 4ºC day/-1ºC night to 28ºC day/22ºC). When the treatment room reached control room conditions (28ºC day/22ºC night), measurements and analyses were started. Results: Low-temperature stress decreased pseudostem length, pseudostem diameter, leaf area, and leaf number of banana clones. The malondialdehyde contents (MDA) were increased compared with control; the chlorophyll content and fluorescence decreased significantly. When temperatures return to normal conditions (28ºC day/22ºC night), only eight banana clones managed to survive and twenty banana clones irreversibly died. After a gradual increase in temperatures, plants have continued to live and form new leaves. Conclusion: At the end of study, it was understood that the low temperatures applied would be sufficient to determine the low-temperature tolerance in banana clones and could work at lower temperatures